Dolor miofascial lumbar en estudiantes de Terapia Física y Rehabilitación de la Universidad Nacional Federico Villarreal, 2012 - Santiago Bazán, Cristhian (2014)
Myofascial lumbar pain in Physical Therapy and Rehabilitation students of Universidad Nacional Federico Villarreal, 2012